A model of the federal funds market: Yesterday, today, and tomorrow - Gara Afonso; Roc Armenter; Benjamin Lester (Federal Reserve Bank of New York, 2018)
The landscape of the federal funds market changed drastically in the wake of the Great Recession as large-scale asset purchase programs left depository institutions awash with reserves and new regulations made it more costly for these institutions to lend. As traditional levers for implementing monetary policy became less effective, the Federal Reserve introduced new tools to implement the target range for the federal funds rate, changing this landscape even more. In this paper, we develop a model that is capable of reproducing the main features of the federal funds market, as observed before and after 2008, in a single, unified framework. We use this model to quantitatively evaluate the evolution of interest rates and trading volume in the federal funds market as the supply of aggregate reserves shrinks. We find that these outcomes are highly sensitive to the dynamics of the distribution of reserves across banks.
Keywords: E42; E43; E44; E52; E58; 330; monetary policy implementation; federal funds market; over-the-counter markets